Batik and its representations: staging of resistance in 20th century colonial Indonesia - Chua, Pei Shyuen (Nanyang Technological University, 2023)
Batik’s significance in Indonesia has been tied strongly to its post-independent narrative and its role in the creation of an Indonesian identity in contemporary discourse but much less is discussed about the period preceding it. This thesis aims to address this gap in literature through exploring the cultural significance of batik and its representations on other forms of material culture during its colonial period in the 20th century as nationalist sentiments were just developing. Working from the perspectives of cultural anthropology and art history, this thesis investigates the use of these visual symbols and signifiers entwined in Indonesian consciousness, as forms of resistance against Dutch colonialism.